(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In this article, a study by the tax authorities of ways to improve the methodological foundations of a desk tax audit and evaluate their effectiveness was carried out, conclusions and suggestions were formed as part of the study.